PENGEMBANGAN MODUL MATEMATIKA YANG BERORIENTASI PADA MODEL PEMBELAJARAN HEURISTIK VEE - Wafa, Ali; Sulisawati, Dwi Noviani; Sujiwo, Dimas Anditha Cahyo (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
Modules are learning resources that are presented in a systematic and planned manner to achieve learning objectives. The research has the aim of improving student's understanding and learning outcomes, by making teaching modules that are directed at the Heuristic Vee learning model. This research was developed using a research and development plomp model which was modified into several stages which included the initial investigation, design, realization/construction, and evaluation and revision tests. Data collection techniques used include test questions, questionnaires, and observations. The research subjects were students of Ambulu Islamic Junior High School class VII A. The quality of the modules developed was seen from the aspect of validity, from material experts it scored 85 very valid predicates, a score of 96 from media experts with very valid predicates, and lesson plans scored 89 very valid predicates. Another instrument that was validated in the form of an observation sheet on the implementation of learning the value of 93 predicates was very valid. In the validation of student activity observations, students scored 92 very valid predicates and teacher activity observation validation scored 92 very valid predicates. In the practical aspect, the results of the observational analysis of the implementation of learning with a score of 89 predicates are very practical. In the student response questionnaire, the score of 88 predicates was very practical, while the teacher's response questionnaire obtained a score of 90 with the very practical predicate. From the aspect of effectiveness, the module development was declared effective based on the results of the pre and post-test analysis which obtained an average increase of 21 so that it had a very effective level. From the results of the analysis of student activities, 91 predicates were very effective. Based on the results of the analysis, it can be concluded that this research resulted in the development of the module which was stated to meet the practical, valid, and effective aspects.